Zooplankton communities and Bythotrephes longimanus in lakes of the montane region of the northern Alps. Issue 1 (2nd January 2017) - Horváth, Zsófia; Vad, Csaba F.; Preiler, Christian; Birtel, Julia; Matthews, Blake; Ptáčníková, Radka; Ptáčník, Robert
Abstract: Lakes in the Alps represent a considerable fraction of nutrient-poor lakes in Central Europe, with unique biodiversity and ecosystem properties. Although some individual lakes are well studied, less knowledge is available on large-scale patterns essential to general understanding of their functioning. Here, we aimed to describe crustacean zooplankton communities (Cladocera, Copepoda) and identify their environmental drivers in the pelagic zone of 54 oligotrophic lakes in the montane region of the Alps (400–1200 m) in Austria, Germany, and Switzerland, covering a spatial scale of 650 km. Moreover, we aimed to provide data on the distribution and ecological requirements of the North American invader Bythotrephes longimanus in its Central European native range. Communities were mainly dominated by widespread species typical of lowland habitats, and only a few true specialists of oligotrophic alpine lakes were present. The most frequent taxa were the Daphnia longispina complex and Eudiaptomus gracilis, with 48 and 45 occurrences, respectively. Species richness decreased with altitude and increased with lake area. The main structuring factors of community composition were chlorophyll a concentration and depth, which drove an apparent separation of mesotrophic and oligotrophic communities. Bythotrephes had 13 occurrences, showing a preference for deep oligotrophic lakes. Its presence was not coupled with lower crustacean species richness, as was repeatedly observed in North America. Additionally, it frequently co-occurred with the other large predatory cladoceran, Leptodora kindtii . B. longimanus might be considered a truly montane species in Central Europe, given its absence in lowland and alpine lakes.